Syari’ah compliance and lawful profit making dilemma in Malaysian Islamic Banks - Waemustafa, Waeibrorheem; Sukri, Suriani (Universiti Malaysia Perlis (UniMAP), 2013)
The significant roles of syari’ah and Islamic banking undeniably critical in order to ensure about compliances to the Islamic principle this in turn provide a very conclusive picture whether Islamic banks truly concerns about Islamic requirement when introducing any type of product that might have any significant effect on its marketability, however the terms used in Islamic banks currently are highly suspicious of being involved in unlawful practices as mentioned in the holy text Al-Quran, this has triggers the increased concerned about the strength of relationship between syari’ah compliance and profitability.The trade-off between profit and syari’ah compliance has remained one of very important issues which they must be addressed to ensure that Islamic banks are not only profit making financial institution but it also very concerns about the roles of Islam and the way that profit is gained to avoid making any profit that against the principle of syari’ah.